2003
DOI: 10.1539/joh.45.300
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cold Exposure and Hypertension

Abstract: The Relationship between Cold Exposure and Hypertension: Joon-Youn KIM, et al. Department of Preventive Medicine, Medical College, Dong-A University, Korea-This study was performed to determine whether there was any relationship between cold exposure and hypertension, and to evaluate risk factors affecting hypertension in cold-exposed workers. In 11 refrigeration industries, 68 male workers working in cold areas more than once per day were selected as the cold-exposed group, and 68 workers not exposed to cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…One of the health hazards of cold exposure is hypertension 79) . Blood pressure is higher in winter than in summer because of the increase in peripheral resistance at lower environmental temperatures 80) , and this may be one of the mechanisms underlying the higher mortality from CVD in winter.…”
Section: Cold Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the health hazards of cold exposure is hypertension 79) . Blood pressure is higher in winter than in summer because of the increase in peripheral resistance at lower environmental temperatures 80) , and this may be one of the mechanisms underlying the higher mortality from CVD in winter.…”
Section: Cold Environmentmentioning
confidence: 99%
“…Blood pressure is higher in winter than in summer because of the increase in peripheral resistance at lower environmental temperatures 80) , and this may be one of the mechanisms underlying the higher mortality from CVD in winter. Long-term occupational exposure to cold environment increases blood pressure in male workers working in cold areas more than once per day 79) . Bortkiewicz et al 34) also found higher blood pressure in workers with exposure to ambient temperatures varying from 0 to 10˚C for 8 h/d than in workers with exposure to ambient temperatures between 10˚C and 14˚C for 8 h/d.…”
Section: Cold Environmentmentioning
confidence: 99%
“…3 Cold winter weather is associated with more severe hypertension, stroke and myocardial infarction in hypertensive patients. 2,4 Seasonal variation of blood pressure (BP), with the highest values during the cold season, has been well documented.…”
Section: Dear Sirmentioning
confidence: 99%
“…[15][16][17][18] Cold temperatures make hypertension more severe in hypertensive patients. 10,14,15,[19][20][21] Chronic cold exposure induces hypertension and cardiac hypertrophy in rats within 1-3 weeks, 22,27,31,32 namely CIH. Cold-induced hypertension is a natural form of experimentally induced hypertension that does not require surgery, administration of large doses of hormones or drugs, or genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%